Estudo experimental de técnicas de medição de descargas parciais nos enrolamentos estatóricos de hidrogeradores - BRASIL, Fernando de Souza (Universidade Federal do Pará, 2014)
This paper aims at analyzing experimental techniques for partial discharges measuring in the stator windings of hydrogenerators. To reach the goal, first proposed a study of the literature on how the structure of the stator windings, with an emphasis on electrical insulation, as well as the concepts of partial discharges and techniques used for measuring in hydrogenerators. It was then mounted in a laboratory arrangement for studying techniques for measuring partial discharges in the stator winding using six different couplers, four conventional capacitive couplers 80, 220, 500 and 1000 pF, and two experimental systems, an antenna, ribbon coaxial cable and RG 58, bare used with the antenna function. The evaluation of the sensitivity of these six systems has been divided in two steps: first were analyzed the responses of couplers applying a known calibration signal, and then analyzed the response of the same high voltage during testing. For application of a known signal calibration the capacitive couplers showed greater sensitivity than antenna and coaxial cable. Already during the response tests showed that the High Voltage sensitivity of the antenna tape is larger than the conventional method of measuring partial discharges in hydro using capacitive couplers 80 and 220 pF. The results obtained in the laboratory showed that the measurement of partial discharges through the antenna tape can be performed satisfactorily in the evaluation of the operating condition of the stator windings of hydro, without either significant loss of sensitivity information or the quantification of the phenomenon.